Comparison of the Organic Farmer’s Crop Production Practices with Prescribedm Standards - B.Savitha; R. Ratnakar (Journal of Agricultural Extension Management, 2025)
This paper studies the status of organic farming in the state of Andhra Pradesh with an objective to compare the agricultural production practices of the organic farmers with the prescribed organic crop production standards. The aim is to find out the deviations in practices followed by the organic farmers from that of the prescribed standards. Findings of the study outline the existing crop production practices of organic farmers under conversion requirements, farm designing, land preparation; seed I plant materials and sowing, crop diversity, weed management, irrigation schedule, fertilization policy, plant protection measures, contamination control, post harvest storage and processing, packaging and labelling, record keeping. The results reveal that the practices of Warangal farmers (71 .88 per cent), East Godavari (60. 94 per cent) and Chittoor (50 per cent) matched with that of prescribed organic crop production standards. However some of the important principles of organic crop production were not taken care of. Hence it is essential for the promoters to educate and create awareness among the organic farmers about organic crop production standards to ensure that they reap the benefits of certification